DYNAMIC GOVERNMENT OF INDIGENOUS VILLAGE IN SOUTHEAST MALUKU - Laimeheriwa, Stefie; Wargadinata, Ella (CosmoGov: Jurnal Ilmu Pemerintahan, 2020)
Research interest in the area of the governance traditional system in modern society is always interesting, especially for Indonesia which was set up above hundred of ethnic groups. The regime shifting gave an impact on the changes of village government policy. It was impact to almost traditional-village government in Indonesia which  transformed into formal-village as National government structure version, although traditional values are still used and mixed therein.. Ohoi is a traditional village in southeast Maluku is one of an example on this compund model. The paper aimed to exlpore the dynamics of Ohoi institutional change  sociologically, economically and politically based on evolutionary social change theory.The study used a qualitative phenomenological approach with informants consisting of  Ohoi’s stakeholders. The results showed that the Ohoi structure changes according to national government policies, however it does not change the social and political value system which is preserving in the Ohoi government system.gb777